(untitled) (Global Journal of Science Frontier Research, 2023)
ABSTRACT Chromosomal polymorphism in Drosophila pseudoobscura has been extensively studied in USA populations and moderately in Mexico with around 60 localities The differences that exist between both entities are notorious in terms of the chromosomal constitution of the populations of each region thus the northern populations USA present as representative inversions the ST AR and CH sequences while in the southern ones Mexico TL CU and SC chromosome arrangements prevail Assuming that a probable mechanism that has allowed this substitution is the flow generated by the presence of clines or gradients in this case with a North-South orientation we set out to find out the existence of these clines with this objective 29 populations of this species distributed in four North- South transects were studied